Nuremberg : The Nazis Facing Their Crimes : [Bonus Features] (Delphis Films : Imavision)
DVD complementario que contiene tres cortometrajes y mediometrajes relacionados con los procesos de Nuremberg: 1. That Justice Be Done; 2. Nazi Concentration Camps; 3. The Atrocities Committed by German-Fascists in the USSR.